The Circulation, Translation, Adaptation, and Production of Vedya’s the Mahabharata and Pramoedya’s Selected Writings - Sophia, Garini Ardya (Indonesian Journal of English Language Studies (IJELS), 2017)
The paper aims to show how non-Western literature works are integrated into World English Literature. It highlights two non-Western literature works, one from India and the other from Indonesia. The object of this study is Mahabharata and Pramoedya’s selected writings. The analysis focuses on comparing them from the process of circulation, translation, adaptation and production to depict the values and portrayal of women in different time spans. The result of the analysis is that the values in Mahabharata are still relevant until today, therefore people may learn from its philosophical life meaning about brotherhood and loyalty. Meanwhile, Pramoedya’s selected writings show the value of nationalism, loyalty, and humanity. The similarities of both literary works also lie in portraying the issue of feminism in responding towards the life challenges.Keywords: world literature, nationalism, feminism, patriarchy, circulation